Paglalarawan ng gunita - Tanierla, Jose Ma. P. (2012)
In this project, the workings of memory specifically forgetting fragments of an event overtime is visually represented through the involvement of the element of time in image-making. Since time is vital to memory, I need to include it as a component, and give it a physical representation. This time element can be simulated through burying the works in soil over a period and allowing the organic components to take their course, thereby allowing decomposition. Decay becomes an index of time. In relation to this, I will be using Transience as theoretical basis. It is referred to as the loss of memory over time. The logic of my processess follows this aspect of memory. The participation of nature - soil and its course - in the process of image-making allows for a random deterioration in various degrees of parts of the works. These works, as a result of such processes may become an important discourse on understanding the idea of memory in relation to the things one forgets and the things one remembers.
"April 2012"
Thesis (BFA)--University of the Philippines Diliman.
Keywords: Memory; Time